2012
DOI: 10.1590/s1984-70332012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Segregation ratios of colored grains in F1 hybrid wheat

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
1
11
0
2
Order By: Relevance
“…Dark (or red) grain varieties were characterized by their high vanillic and ferullic acid content, which is possibly linked to the vanilla odour [17]. Dark grain colour is due to anthocyanin stored in the pericarp and the testa [18] [19]. Anthocyanins are known to affect sensory characteristics.…”
Section: Overall Discussionmentioning
confidence: 99%
“…Dark (or red) grain varieties were characterized by their high vanillic and ferullic acid content, which is possibly linked to the vanilla odour [17]. Dark grain colour is due to anthocyanin stored in the pericarp and the testa [18] [19]. Anthocyanins are known to affect sensory characteristics.…”
Section: Overall Discussionmentioning
confidence: 99%
“…Analysis of nutrient composition of purple wheat shows that the amount of 40 kinds of nutrients is higher than those of the control (GUO et al, 2012;GUO et al, 2013). For example, the amounts of sodium and manganese in purple wheat are higher than the standards by 312 -2018% and 548 -733%, respectively.…”
Section: Coloured Wheat Seeds For Nutritionmentioning
confidence: 90%
“…"Black" (deep purple) hues of wheat kernel colour can be due to the combination of anthocyanin genes for blue pericarp and blue aleurone (LI et al, 2005). Results of GUO et al (2012) showed that the colour inheritance of purplegrained wheat follows a maternal inheritance pattern and that the blue-grained wheat expresses xenia in most cases.…”
Section: Origin and Genetic Control Of The Seed Colourmentioning
confidence: 99%
See 1 more Smart Citation
“…The negatively charged phosphate group in phytate strongly binds to divalent cations such as Ca 2+ , Fe 2+ , K 2+ , Mg 2+ and Zn 2+ at physiological pH to form a mixed salt called phytin which reduces the bio-availability of micronutrients to humans and monogastric animals (Greiner and Konietzny, 2006). This leads to Fe and Zn deficiency in human population making them prone to several diseases (Guo et al, 2012). This problem is more common in infants and pregnant women who require relatively more quantity of micronutrients.In addition, some monogastric animals are not able to metabolize phytic acid due to the lack of sufficient level of phytate hydrolysing enzymes activity in their digestive tract and as a result the feed of these animals are enriched with phosphorus.…”
Section: Introductionmentioning
confidence: 99%